Prognostic factors for complications in patients with pancreatic pseudocyst - Manuel Alejandro Martínez Corrales; Leonila Noralis Portal Benítez; Yoisel Duarte Linares; Joaquín Zurbano Fernández (Medisur, 2023)
Background: pseudocysts of the pancreas appear as a complication in acute and chronic pancreatitis, as well as in pancreatic trauma. Sometimes they go unnoticed, due to their asymptomatic nature in some cases, in addition to the poorly defined clinical picture. The studies oriented to this subject allow a satisfactory management of the patients diagnosed with said entity. Objective: to determine the prognostic factors for complications in patients with pancreatic pseudocyst. Methods: a longitudinal descriptive study was carried out in patients with pancreatic pseudocysts treated at the Arnaldo Milián Castro Hospital, in Villa Clara, from January/2013 to December/2020, 45 patients were the sample. Results: patients aged 40-59 years old (57.8%), and males (62.2%) predominated. The fundamental cause was acute pancreatitis (51.1%), and the most frequent location was the pancreatic body (37.8%). The most observed symptom was abdominal pain (82.2%). Medical management was performed in most of the patients (75.6%) and cystogastrostomy in 13.3%. 68.9% evolved without complications. Only 3 patients died (6.7%). Age greater than 52 years old, formation time greater than six weeks, size less than 6 centimeters, and persistence had Odds Ratio values: 1.214- IC(0.211-6.985); 7,250- CI(0,786-66,842); 4.688-CI(0.489-44.904); and 2.875-CI(0.479-17.239), respectively. Conclusions: age greater than 52 years old, formation after six weeks, size less than six cm, and persistence greater than three weeks are risk factors for complications of pancreatic pseudocyst.